Mitigation of Methotrexate-Induced Intestinal Mucositis in Male Wistar Rats by Gallic Acid: The Role of HGF and C-Met Genes - Reza Norouzirad; Khashayar Zahedi; Mohammad Mehdi Behvandi; Abbas Moridnia; Susan Sabbagh (Journal of Toxicology)
Conclusion: GA could increase HGF and C-met expression, decrease inflammatory cytokines, and improve histological injuries, affected by MTX, indicating a beneficial role for GA following GI-M.